PENELITIAN TINDAKAN KELAS UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN KEPERAWATAN MATERNITAS - Ratna Hidayati (STIKES dan AKZI Karya Husada Kediri, 2023)
The shift in the learning process due to the pandemic is needed online, requiring the creativity of lecturers to achieve learning goals. The purpose of this study is to find a bold learning model that is effective in learning achievement. This research method: Classroom Action Research includes planning, implementing, observing and evaluating the process and results of actions, reflecting and so on until learning outcomes are achieved. Sampling is total sampling in the third semester students bachelor of nursing study program Institute of Health Sciences Karya Husada Kediri as much 86 people. Evaluation of learning outcomes is done online, assignments, observations and attendance. The results of the study that the online learning model took place effectively in the third semester of nursing students. Students can access shared materials and videos to repeat study independently. Learning outcomes increased from cycle 1 to cycle 2 and so on from the initial average value of 55 to 60, 70, 80 and so on. Meanwhile, nursing skills, which were originally competent students from 5 became 10 and decreased again to 3 in the newborn baby resuscitation technique (a more advanced technique). difficult). The total value of theory and laboratory is an average of 80.The online method with innovation and a combination of assignments, pre-tests, quizzes and post-tests as well as modifications with blended learning is effective in increasing learning outcomes both knowledge and skills in maternity nursing courses.It is necessary to develop a method to adjust the situation. conditions and needs of students.